Employee perceptions of share ownership schemes: An empirical study - N. E. Mazibuko; C. Boshoff (South African Journal of Business Management, 2003)
The objective of this study was to investigate some of the problems associated with the introduction and successful management of Employee Share Ownership Schemes (ESOPs). An ESOP is a participative management approach that appeals to some of the needs of both employees and management. The study considered how perceptions of ESOPs can be influenced and managed through managerial antecedents such as trust, empowerment and communication, and empirically measures their impact on outcome variables such as organisational commitment.The empirical findings revealed that if employees have positive perceptions of their firm's ESOP (the value and benefit for them) they are more likely to be committed to their firm (organizational commitment) and organizational commitment has been shown to lead to a host of benefits for the firm.
Keywords: 650